Answer:
g(x) = 3(x-9)(x-5)
Zeros: x = 9 and x = 5.
Step-by-step explanation:
Given a second order polynomial expressed by the following equation:
[tex]ax^{2} + bx + c, a\neq0[/tex].
This polynomial has roots [tex]x_{1}, x_{2}[/tex] such that [tex]ax^{2} + bx + c = a(x - x_{1})*(x - x_{2})[/tex], given by the following formulas:
[tex]x_{1} = \frac{-b + \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]x_{2} = \frac{-b - \sqrt{\bigtriangleup}}{2*a}[/tex]
[tex]\bigtriangleup = b^{2} - 4ac[/tex]
In this question:
[tex]g(x) = 3x^{2} - 42a + 135[/tex]
So
[tex]a = 3, b = -42, c = 135[/tex]
[tex]\bigtriangleup = (-42)^{2} - 4*3*135 = 144[/tex]
[tex]x_{1} = \frac{-(-42) + \sqrt{144}}{2*3} = 9[/tex]
[tex]x_{2} = \frac{-(42) - \sqrt{144}}{2*3} = 5[/tex]
So
g(x) = 3(x-9)(x-5)
Zeros: x = 9 and x = 5.